Monitoring Of Water Quality In Vanamei Shrimp (Litopenaeus vannamei) Farming In Cv. Cemarasewu Sumber Rejeki, Cilacap - Mia Pinandita; Dewi Nugrayani; Imam Marzuki (PT. Artha GenetikaLab Indonesia, 2025)
Pacific White Shrimp (Litopenaeus vannamei) is a frequently cultivated shrimp species. This is because it offers promising prospects and profits. Superior vannamei can be produced by considering several aspects of the cultivation process. Internal factors include the origin and quality of the seeds, as well as external factors, including cultivation water quality, feeding, technology, and pest and disease control. This research was conducted from September 15 to October 15, 2022, at CV. Cemarasewu Sumber Rejeki, Jetis Village, Cilacap, Central Java. The purpose of this study was to determine the water quality conditions in Pacific White Shrimp rearing ponds at CV. Cemarasewu Sumber Rejeki, Cilacap. Three ponds were used for data collection: plots B13, B14, and B15, with shrimp rearing ages of 100-129 days. Research results indicated that plots B13, B14, and B15 at CV. Cemarasewu Sumber Rejeki provides good water quality for Pacific White Shrimp cultivation. The results of water quality parameters measured in this study include: brightness up to 35 cm, temperature ranging from 27-29 ºC, pH ranging from 7.6-8.3, salinity ranging from 14-22 ppt, alkalinity ranging from 125-169.6 ppm, TOM ranging from 70.4-79.2 ppm, DO ranging from 4.32-4.98 ppm, phosphate ranging from 0.25-0.5 ppm, nitrite ranging from 0.013-0.085 ppm, nitrate 0 ppm, ammonia ranging from 0.00-0.085 ppm, ammonium ranging from 0.00-0.50 ppm and plankton ranging from 2,500-282,500. It can be concluded that the water quality in pond plots B13, B14, and B15 at CV. Cemarasewu Sumber Rejeki meets the appropriate standards to support Pacific white shrimp cultivation.